2021
DOI: 10.1002/pa.2802
|View full text |Cite
|
Sign up to set email alerts
|

The external debt‐inflation nexus in Egypt

Abstract: Egypt has a long history with external financing dating back to the 19th century. Nevertheless, Egypt's external debt has been mounting remarkably in the past few years. This paper examines the impact of Egypt's external debt on its price level, a topic ignored by researchers. Nonetheless, as inflation is a hydra‐headed problem, this paper develops several models which incorporate fiscal and monetary policies besides other inflation‐inducing internal and external factors using monthly data extending from 2000M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…This result is in line with the findings of Abate (2020) of a long-run positive relationship between money supply and inflation in Ethiopia from 1985 to 2018. It also aligns with the findings of Kumar and Dash (2020) in India and Helmy (2022), who found money supply to have a statistically significant positive impact on inflation in Egypt in the long run, using quarterly data from 2000 to 2020. Also, this monetary theory of inflation is supported by the findings of Benati (2021), who used data on 27 countries and found a one-for-one relationship between broad money growth and long-term inflation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result is in line with the findings of Abate (2020) of a long-run positive relationship between money supply and inflation in Ethiopia from 1985 to 2018. It also aligns with the findings of Kumar and Dash (2020) in India and Helmy (2022), who found money supply to have a statistically significant positive impact on inflation in Egypt in the long run, using quarterly data from 2000 to 2020. Also, this monetary theory of inflation is supported by the findings of Benati (2021), who used data on 27 countries and found a one-for-one relationship between broad money growth and long-term inflation.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, Benati (2021) used data from 27 countries and found a one-for-one relationship between broad money growth and long-term inflation. For additional evidence on the role of money supply in inflation, see the findings of Abate (2020) for Ethiopia, Kumar and Dash (2020) for India, and Helmy (2022) for evidence in Egypt.…”
Section: Methodsmentioning
confidence: 99%
“…The study found public debt to have a positive and significant effect on inflation for GMM estimates while PMG estimation indicated that public debt is deflationary in the short run but inflationary in the long run. Equally, Heba (2021) found that external debt elevates prices both in the short and long runs in Egypt. His findings are consistent with that of Aisen, & Veiga (2006) who conclude that external finance deficit increases both inflation and interest rates.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…2(2) 17-23, 2023 external debt decrease when the inflation rate increase. Helmy (2021) using Egypt as a case study concludes that in the short run and long run, external debt deteriorates inflation. Similarly, Boshra (2023) indicates that in both the short and long run, inflation has a decreasing impact on external debt.…”
Section: Literature Review Theoretical Literaturementioning
confidence: 99%
“…Moreover, developing economies often grapple with substantial external debt, exposing them to fluctuations in global financial markets. This susceptibility can create difficulties for central banks as they endeavor to oversee and stabilize domestic inflation rates [ 6 , 7 ]. Furthermore, in developing economies, reduced central bank credibility leads expectations to be anchored in historical data, thereby increasing their reliance on past information.…”
Section: Introductionmentioning
confidence: 99%